Incidence of packaging on the organoleptic quality of four brands of chocolate produced in the Amazonas Region - Bustos Chavez, Meliza del Pilar; Rituay Trujillo, Pablo-Alfredo; Montes de Oca Rojas, Yorberth Yannedy; Arias Vargas, Francisco Javier; Campos Trigoso, Jonathan-Alberto (Journal of business and entrepreneurial studie, 2023)
The first impression on consumers is the packaging of the product, through the extrinsic characteristics consumers generate expectations that influence the evaluation of the product and determine the probability of purchase. Therefore, the objective of this study was to determine the incidence of packaging on the organoleptic quality of four brands of chocolates that are produced in the Amazon region, under three phases (i) packaging condition, where the effect of packaging characteristics on the consumer's visual perception without tasting the chocolate was studied, (ii) blind condition without packaging, in which the organoleptic quality of each chocolate was determined using the sensory quality index, (iii) and the reported condition, evaluated the combined effect (first and second phase) determining the level of satisfaction, tastes, and preferences to finally measure the degree of incidence of the packaging design of the chocolates on the organoleptic quality in the four brands using Spearman's Correlation Coefficient. The degree of incidence between the design and the organoleptic quality with the highest significance was in the Palerca chocolate in the factors of; innovation in the shape of the packaging and the aroma of the chocolate (r= 0.6503), warmth in the color concerning the flavor of the chocolate (r= 0.6289), and the quality factor in the function of the color and aroma of the chocolate (r= 0.6163).